1973
DOI: 10.1128/aac.3.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Silver Sulfadiazine: Effect on the Ultrastructure of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa exposed to silver sulfadiazine (AgSu) were examined in an electron microscope. The treated cells were distorted in shape, and structures (blebs) protruded from the cell surface. These "blebs" appeared to arise from the cell wall. A strain of P. aeruginosa resistant to AgSu did not display these changes. Upon exposure of P. aeruginosa to silver nitrate, none of these changes was seen; rather, such cells are characterized by large, central aggregations of nuclear material. The results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
2

Year Published

1973
1973
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 12 publications
2
36
0
2
Order By: Relevance
“…Although it has been suggested that binding to DNA is the mode of action in vivo [18], other workers suggest that Ag 2 binds preferentially to external cell structures and that only small amounts are bound to DNA [24]. Cells of S. aureus treated with AgSD were enlarged, some retraction of the cytoplasmic membrane from the cell wall was seen and division planes between bacteria became indistinct, supporting the view that the effect is on external cell structures [26]. Studies have shown that subinhibitory levels of sulphadiazine affect membrane permeability [27].…”
Section: Introductionsupporting
confidence: 54%
“…Although it has been suggested that binding to DNA is the mode of action in vivo [18], other workers suggest that Ag 2 binds preferentially to external cell structures and that only small amounts are bound to DNA [24]. Cells of S. aureus treated with AgSD were enlarged, some retraction of the cytoplasmic membrane from the cell wall was seen and division planes between bacteria became indistinct, supporting the view that the effect is on external cell structures [26]. Studies have shown that subinhibitory levels of sulphadiazine affect membrane permeability [27].…”
Section: Introductionsupporting
confidence: 54%
“…Rosenkranz and Carr found that most silver was associated with the cell membrane (and proteins), and some with the cell wall (43). They further examined AgSu treated bacteria by electron microscopy, and observed them to be distorted in shape, with surface blebs (45). A strain resistant to AgSu did not display surface blebs.…”
Section: Water Sterilizationmentioning
confidence: 99%
“…AgSu has a broad spectrum of action, and most microorganisms capable of infecting burns and wounds are susceptible to the antimicrobial action of the drug at levels which are readily obtainable topically (2,19). The mechanism of action of AgSu was studied mainly in Pseudomonas aeruginosa where it affects primarily the external cell structure (3,12,14 (Ag/ml) CB synthetic medium (medium HA, ref. 13).…”
mentioning
confidence: 99%